2012
DOI: 10.1039/c2lc40459a
|View full text |Cite
|
Sign up to set email alerts
|

An integrated fiber-optic microfluidic device for detection of muscular force generation of microscopic nematodes

Abstract: This paper reports development of an integrated fiber-optic microfluidic device for measuring muscular force of small nematode worms with high sensitivity, high data reliability, and simple device structure. A moving nematode worm squeezed through multiple detection points (DPs) created between a thinned single mode fiber (SMF) cantilever and a sine-wave channel with open troughs. The SMF cantilever was deflected by the normal force imposed by the worm, reducing optical coupling from the SMF to a receiving mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…As a result, it is applied to study the nematode. The nematode has the same locomotion pattern as C. elegans such as Oesophagostomum species parasites of humans [ 29 ]. Furthermore, a basic principle of our method is the same as a strain gauge, therefore it can be used as a sensor to detect the environment in a microfluidic device such as pressure in a micro channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is applied to study the nematode. The nematode has the same locomotion pattern as C. elegans such as Oesophagostomum species parasites of humans [ 29 ]. Furthermore, a basic principle of our method is the same as a strain gauge, therefore it can be used as a sensor to detect the environment in a microfluidic device such as pressure in a micro channel.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, research has focused on characterizing the locomotion of C. elegans [ 25 , 26 , 27 ]. The use of microfluidic devices for the study of C. elegans locomotion has successfully investigated its locomotion, and additionally, its force level [ 24 , 28 , 29 ], adaptability [ 30 ], and behavior [ 19 ]. In these works, the use of an imaging system and software to observe the undulatory locomotion of C. elegans limited the size of the observing system, therefore, making it difficult to develop a small and portable biological assay for C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics-based biotechnologies have been extensively developed to enable system miniaturization, automation, and parallelization of biochemical processes, 19 as well as highthroughput culture, manipulation, and detection of cells and microorganisms. [20][21][22][23][24][25][26] Several microfluidic devices have been reported for on-chip cultivation, analysis, and transformation of microalgal cells under various growth conditions. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] For example, toxicity screening using marine microalgal cultures in a microfluidic device was reported.…”
Section: 064104-1mentioning
confidence: 99%
“…Microfluidics technology has been the focus of intense research and development as it promises a multitude of advantages in a number of markets including chemical and biological analysis (Shih et al 2015 ; Liberale et al 2013 ), drug delivery (Majedi et al 2013 ) and medical diagnose (Lee et al 2014 ; Ng Alphonsus et al 2010 ), such as small sizes, high throughput and low cost of microfluidic systems (Paul et al 2006 ). Microfluidic has also revolutionized some aspects of optical area (Tseng et al 2009 ; Liu et al 2012 ). Lim et al ( 2014 ) reported a microfluidic optical fiber devices composed of microfluidic channels which can be used for sensitive refractive index sensing and biosensing applications.…”
Section: Introductionmentioning
confidence: 99%